Exploring older adults' understandings of disaster preparedness : a New Zealand perspective : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Manawatū, New Zealand - Tuohy, Robyn Jean (Massey University, 2014)
Individual preparedness for a disaster has centred on educating and encouraging people to protect themselves against injury and damage to assist with response and recovery after a disaster. Research on factors influencing individual disaster preparedness has focused on demographic and psychological variables, while socio-cultural contexts have received less attention. These omissions may help explain why more vulnerable population groups are disproportionately affected. Older adults are a rapidly increasing population group who are a vulnerable group at greater risk of negative effects during and after a disaster; however, little attention has been given to older adults’ perspectives about disaster preparedness. This thesis is presented as four papers written for submission to peer reviewed journals, and explores older adults’ meanings and experiences about disaster preparedness from a social constructionist perspective. A series of 26 qualitative interviews using a narrative methodology was undertaken in 2012 with participants located in Wellington and Christchurch (median ages 84, and 80), New Zealand. Participants were recruited through a home support agency. Inductive thematic analysis of the data sets was undertaken, which attended to the influences of personal and socio-cultural contexts on disaster preparedness. The first paper provides a conceptual argument for use of qualitative methodologies to further explore understandings of disaster preparedness. The second paper focuses on older adults’ household disaster preparedness in Wellington, which identified that older adults accepted personal responsibility for assembling and maintaining their survival kits. Practical concerns such as the ability to refill water bottles, monitor stock rotation, and ensure adequate medication supplies were identified to be difficult for some. Preparedness was also associated with the quality of supportive social relationships that could provide assistance. The third paper is also based on the Wellington study, and provides a broader discussion about everyday preparedness. Meanings and experiences of preparedness were concerned with managing health decline, preparing for death, and the interpersonal complexity of negotiating their personal and social needs to remain independent in the community. The fourth paper discusses older adults’ experiences of preparedness during the Canterbury earthquake sequence (2010-2012). Disaster preparedness was primarily linked to the importance of social relationships; and a concern regarding a lack of age appropriate safety messages about personal protection. This thesis contributes to the literature on disaster preparedness by identifying age specific influences, which relate to managing personal health, social support and socio-cultural norms of independence. Some participants lacked informational, health and social resources, which would enable preparedness actions and the ability to respond effectively. The research from the Wellington and Christchurch studies identifies the need for coordinated, multidisciplinary age specific disaster preparedness planning to assist individual and community resilience.
Keywords: Disaster preparedness; Emergency management; Older adults; Older people; Household disaster preparedness